Product Lifecycle Knowledge Management for SMEs: Development of a cloud-based Collaboration Platform using Social Software - Hefler, Lennart (2016)
This dissertation investigates how social software techniques can facilitate product lifecycle and knowledge management for small and medium-sized enterprises. In order to explore those aspects, literature from theory and practice are analysed critically, revealing an extensive research gap at the point of intersection of those three topics. A structured and detailed analysis of relevant literature in regards to the requirements of SMEs serves as the foundation for a proposed software solution. While the findings highlight the importance of user-experience and collaboration, it is revealed that social software can satisfy most of their requirements. Consequently, a potential product lifecycle knowledge management platform is introduced along its infrastructure and functionalities and illustrated through prototype wireframes. Under closer examination of the larger ramifications, product lifecycle management systems need to offer appropriate interfaces to external applications while offering as much flexibility to the user as possible. Nevertheless, as web-systems are evolving constantly, future research in the area of product lifecycle and knowledge management should consider modern technologies including software as a service, micro-services as well as big data analytics.